A Strategy Framwork For Deciding Between Alliances Or Acquisition Of Johnson & Johnson Pharmaceutical Company (Case Study: Strategy Farmwork of Johnson & Johnson And Cipla Inc in The Production of Anti-Infectious Drugs) - Nur Aini Fitriya Ardiani Aniqoh (Journal of Digital Marketing and Halal Industry, 2019)
This study analyzes a strategy framwork for deciding between alliances or acquisition of Johnson Johnson Pharmeutical Company. The general objective of this study is to determine the appropriate corporate development strategy of Johnson Johnson to strengthening the position in the area of infectious diseasese to help the mankind to get the best anti infectious drugs with the affordable price. Infectious diseases is a second leading killer worldwide, it is consist of HIV/ AIDS, TB, Hepatitis C, etc. Infectious diseases have caused an unprecedented global health crisis. The Asia division of Johnson Johnson plans to invest in open innovation through more research partnerships and collaborative efforts that connect the medical and academic communities to its RD centers especially in infectious disease. The data used in this research is data result of observation, literature study and interviews with senior executives and consultants who  handle comparable decision of JohnsonJohnson. The data show that alliance is preferrable. High uncertainty within the environment is the most influencing factor to determine this choice. Due to the industry nature, many RD collaborations in developing particular drugs are established. By defining the proper governance structure the collaboration can limit the risk of losing in the learning race and core competencies spillover while obtaining the knowledge access to the counterparty. The Strategic alliance between Johnson Johnson and Cipla Inc can help them toughen the corporate development strategy. Because of their similarities in the production of anti-infectious drugs, they can cooperate to penetrate emerging markets and do several RD collaborations to create a competitive advantage.